Factors associated with malaria parasitaemia among children under 5 years in Uganda: a secondary data analysis of the 2014 Malaria Indicator Survey dataset - Humphrey Wanzira; Henry Katamba; Allen Eva Okullo; Bosco Agaba; Mathias Kasule; Denis Rubahika (Malaria Journal, 2017)
Abstract Background In the midst of success with malaria reduction in Uganda, there are areas that still have high prevalence of malaria parasitaemia. This project aimed at investigating factors associated with this prevalence and its relationship with anaemia. Methods This is a secondary data analysis of the 2014 Malaria Indicator Survey dataset of children under 5 years. All had a blood sample taken by finger or heel prick for determination of malaria parasitaemia and estimation of haemoglobin level for anaemia status. The main outcome was the presence of malaria parasitaemia by microscopy and independent variables included: age, gender, residence (urban vs rural), use of a long-lasting, insecticidal-treated net, indoor residual spraying (IRS) of household in the past 6 months, mother’s highest education level, mother heard malaria prevention message in the past 6 months, and household wealth status. Results The analysis included 4930 children and of these, 938 (19.04%: 95% CI 16.63–21.71) tested positive for malaria parasites. Malaria parasite prevalence significantly increased from 11.08 (95% CI 9.12–13.40) among children with no anaemia to 50.99% (95% CI 39.13–62.74) with severe anaemia (Chi-square p-value = 0.001). Additionally, prevalence significantly rose from the youngest age group (under 6 months) by 1.62 times (95% CI 1.04–2.52, p = 0.033) among the age group of 7–12 months and to four times (95% CI 2.57–6.45, p = 0.001) among those who were between 49 and 59 months. The following were associated with reduced parasitaemia: IRS use (AOR 0.23 [0.08–0.61], p = 0.004), educated mothers (primary AOR 0.75 [0.59–0.96], p = 0.023 to tertiary AOR 0.11 [0.02–0.53], 0.006), mother heard malaria message (AOR 0.78 [0.62–0.99], p = 0.037), and wealthier households (richest AOR 0.17 [0.08–0.36], p = 0.001). Conclusions Increasing malaria parasite prevalence among children under 5 years is still related to increasing age and severity of anaemia even in the context of decreasing malaria prevalence. Designing ...